Robotic system and method of use - GETTINGS ADAM M (2013)
A method of using a robotic vehicle system is described. The method can include delivering a force through a robotic vehicle system powertrain in the robotic vehicle system. The force delivery can include generating a force with a force generation component in the robotic vehicle system. The force delivery can also include delivering the force through a first shaft to a first receiver and delivering the force from the first receiver to a second receiver. The first shaft can interface with the first receiver.